2021
DOI: 10.1155/2021/8867185
|View full text |Cite
|
Sign up to set email alerts
|

Research on Carrying Capacity of T‐Shaped Stiffened Concrete‐Filled Steel Tubular Columns Subjected to Eccentrically Compressive Load

Abstract: In this paper, in order to further study the mechanical behavior of T-shaped stiffened concrete-filled steel tubular (CFST) columns, numerical programs of eccentrically compressive T-shaped stiffened CFST columns were developed to calculate moment M-ϕ curvature curves of cross section and column. The calculated curves with the numerical programs agree well with the experimental results. A parametric analysis was carried out to calculate M-N correlation curves of cross section and column to investigate influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To address this issue, L-shaped, T-shaped, and cross-shaped CFSTs have increasingly emerged as a primary research focus in the realm of steel-concrete composite structures. [6][7][8] While conventional specially shaped CFSTs (Figure 1a) can effectively resolve the problem of protruding column edges, numerous research results indicate that the steel plates at their concave side are susceptible to significant deformation and damage under loading, resulting in a substantial reduction in the members' bearing capacity and ductility. 9,10 To augment the constraining influence of uniquely shaped steel tubes on concrete, scholars have proposed various structural measures (e.g., adding stiffening ribs, [11][12][13][14][15] installing restraint bars, [16][17][18] and using combinations of multiple rectangular steel tubes [19][20][21][22][23] ) to delay or prevent local buckling, as depicted in Figure 1b,d.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, L-shaped, T-shaped, and cross-shaped CFSTs have increasingly emerged as a primary research focus in the realm of steel-concrete composite structures. [6][7][8] While conventional specially shaped CFSTs (Figure 1a) can effectively resolve the problem of protruding column edges, numerous research results indicate that the steel plates at their concave side are susceptible to significant deformation and damage under loading, resulting in a substantial reduction in the members' bearing capacity and ductility. 9,10 To augment the constraining influence of uniquely shaped steel tubes on concrete, scholars have proposed various structural measures (e.g., adding stiffening ribs, [11][12][13][14][15] installing restraint bars, [16][17][18] and using combinations of multiple rectangular steel tubes [19][20][21][22][23] ) to delay or prevent local buckling, as depicted in Figure 1b,d.…”
Section: Introductionmentioning
confidence: 99%
“…The research indicated the setting of the binding bars delays the local buckling and contributes to the improved bearing capacity and ductility. Yang [9] carried out a series of mechanical tests on SS-CFST composite columns with stiffeners, as illustrated in Figure 1g-i. The stiffeners have little impact on the bearing capacity but enhance the contact between the steel tube and the concrete and eliminate the steel tube and concrete separation at the concave corner.…”
Section: Introductionmentioning
confidence: 99%